Modeling the Simultaneous Dropout of Energetic Electrons and Protons by Magnetopause Shadowing - Xingzhi Lyu; Weichao Tu; Jinbei Huang; Qianli Ma; Zhi‐Gu Li (Geophysical Research Letters, 2024)
Abstract Magnetopause shadowing (MPS) effect could drive a concurrent dropout of radiation belt electrons and ring current protons. However, its relative role in the dropout of both plasma populations has not been well quantified. In this work, we study the simultaneous dropout of MeV electrons and 100s keV protons during an intense geomagnetic storm in May 2017. A radial diffusion model with an event‐specific last closed drift shell is used to simulate the MPS loss of both populations. The model well captures the fast shadowing loss of both populations at L* > 4.6, while the loss at L* < 4.6, possibly due to the electromagnetic ion cyclotron wave scattering, is not captured. The observed butterfly pitch angle distributions of electron fluxes in the initial loss phase are well reproduced by the model. The initial proton losses at low pitch angles are underestimated, potentially also contributed by other mechanisms such as field line curvature scattering.